Oxygen toxicity and hemoglobinemia in subjects from a highly polluted town - Medeiros, Marisa H.G.; Bechara, Etelvino J.H.; Naoum, Paulo Cesar [UNESP]; Mourão, Celso Abbade [UNESP] (Taylor & Francis, 1983)
Red blood cell activities of superoxide dismutase and glutathione peroxidase, two key enzymes responsible for the control of the concentrations of activated oxygen species, were approximately two-fold higher in residents of Vila Parisi (Cubatão, Brazil)—a higher polluted neighborhood—than in a population sample from São Paulo City. The catalase levels were the same in both samples. A concurrent high concentration of methemoglobinemia and sulfhemoglobinemia was encountered in the blood of Vila Parisi residents. These data raise the possibility that the increased rate of oxyhemoglobin oxidation yielding O2and H2O2 may be relevant to mutagenesis induced by HO° radicals. © 1983 Taylor and Francis Group, LLC.